The UBC-40 Urothelial Bladder Cancer cell line index: a genomic resource for functional studies. (December 2015) - Earl, Julie; Rico, Daniel; Carrillo-de-Santa-Pau, Enrique; Rodríguez-Santiago, Benjamín; Méndez-Pertuz, Marinela; Auer, Herbert; Gómez, Gonzalo; Grossman, Herbert; Pisano, David; Schulz, Wolfgang; Pérez-Jurado, Luis; Carrato, Alfredo; et al.
Abstract Background Urothelial bladder cancer is a highly heterogeneous disease. Cancer cell lines are useful tools for its study. This is a comprehensive genomic characterization of 40 urothelial bladder carcinoma (UBC) cell lines including information on origin, mutation status of genes implicated in bladder cancer (FGFR3, PIK3CA, TP53, andRAS ), copy number alterations assessed using high density SNP arrays, uniparental disomy (UPD) events, and gene expression. Results Based on gene mutation patterns and genomic changes we identify lines representative of theFGFR3 -driven tumor pathway and of theTP53/RB tumor suppressor-driven pathway. High-density array copy number analysis identified significant focal gains (1q32, 5p13.1-12, 7q11, and 7q33) and losses (i.e. 6p22.1) in regions altered in tumors but not previously described as affected in bladder cell lines. We also identify new evidence for frequent regions of UPD, often coinciding with regions reported to be lost in tumors. Previously undescribed chromosome X losses found in UBC lines also point to potential tumor suppressor genes. Cell lines representative of theFGFR3 -driven pathway showed a lower number of UPD events. Conclusions Overall, there is a predominance of more aggressive tumor subtypes among the cell lines. We provide a cell line classification that establishes their relatedness to the major molecularly-defined bladder tumor subtypes. The compiled information should serve as a useful reference to the bladder cancer research community and should help to select cell lines appropriate for the functional analysis of bladder cancer genes, for example those being identified through massive parallel sequencing.